Personal and shared knowledge building in P2P semantic wikis - Torres, Diego; Skaf-Molli, Hala; Díaz, Alicia Viviana; Molli, Pascal (2009)
Semantic Wikis [1-3] are one of the most successful Semantic Web applications. They are widely used for collaborative knowledge management. In semantic wikis, wikis pages are annotated with semantic data to facilitate the navigation, the information retrieving and ontology emerging. Semantic data represent the shared knowledge base which describes the common understanding of the community. The knowledge base is built collaboratively through an iterative and social process. However, as knowledge is basically created by individuals [4], it is fundamental to support personal knowledge management [3]. Personal Semantic Wikis [3] provide an easy way to manage personal knowledge without collaboration supports. But, in their daily activities, to carry out a collaborative knowledge building activity, users need to manage both shared and personal knowledge. Collaborative knowledge building [5, 4] is a spiraled process which involves externalization, publication, internalization and reaction. Collaborative knowledge building systems support partially or completely this process. Although the semantic wiki systems are more appropriated to support
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
European Semantic Web Conference (ESWC 2009). (6º : 2009 : Heraclión, Grecia)
Keywords: WEB SEMÁNTICA; WIKIS